Cultural and support environmental services: perception by family farmers in agroforestry systems in Brazil and Costa Rica (Research, Society and Development, 2020)
Many family farmers who manage agroforestry systems (AS), also handle a range of environmental services (ES), however, few studies the human perceptions about the ES. Therefore, this study aimed to verify if environmental services (cultural and support) are perceived by family farmers who manage agroforestry systems in Mato Grosso do Sul (BR) and Cartago (CR). The data were collected through a questionnaire drawn up with 18 questions divided in 2 categories of environmental services classified by the Millennium Ecosystem Assessment. It is believed that family farmers who own AF are agents of biodiversity, because through its religious and traditional conceptions, they realize the ES and regard them as important by favouring your well-being, keeping them always motivated. Such studies are relevant and can provide subsidies to public policy development for conservation and valuation of biodiversity, as well as assist projects for payment for environmental services.